A salt-free and chromium discharge minimizing tanning technology: the novel cleaner integrated chrome tanning process. (20th January 2016) - Zhang, Chunxiao; Lin, Jiang; Jia, Xinju; Peng, Biyu
Abstract: Chrome tanning is the most important and widely used tanning method in leather manufacture up to now. However, simultaneously control of the severe contamination of large amount of chromium and chloride discharge, both of which are serious environmental concerns, is highly challenging with the conventional chrome tanning process. Consequently, the development of leather manufacture is being unsustainable. In order to minimize the emissions of chromium and chloride integrately, a salt-free and high exhaustion chromium tanning method was designed and optimized in both laboratory and pilot scale. The results indicated that, being superior to the conventional process, the chrome tanning process was conducted in a salt-free condition smoothly and the chromium absorbility was increased to 98% from 73% in the novel process. Then the Cr dosage was minimized from 1.16% to 0.61% and the residual Cr concentration in the spent liquor dropped below to 50 mg/L from above 1100 mg/L. The pilot-scale experiments verified that the novel method was acceptable in the aspects of organoleptic and mechanical properties of resultant leather, product style and cost. It is anticipated that the spent liquor containing a very small amount of chrome and chloride can be more easily disposed and the generation of chromium-containing sludge will be stoichiometrical much less. The established novel chrome tanning process satisfactorily solves the longstanding problems commercially and matches the integral requirements of the modern sustainable leather industry. Graphical abstract: Highlights: The novel process resolves a century problem satisfactorily in leather industry. No common salt is needed any more in pickling–chrome tanning process. The chromium absorbility is increased from 73% to 98% by the novel process. The chromium concentration of chrome tanning waste water is dropped to below 50 mg/L. Being commercially viable, the novel process reduces Cr offering by 30% nearby.